Fall Detection for The Elderly People - Khunteta , Ajay; Sharma , Abhishek (International Journal of Basic and Applied Sciences, 2025)
Typically, research and industry presented various practical solutions for assisting the elderly and their ‎caregivers against falls via detecting falls and triggering notification alarms calling for help as soon as falls ‎occur to diminish fall consequences. Furthermore, fall likelihood prediction systems have  ‎emerged lately based on the manipulation of the medical and behavioral history of elderly patients in order to ‎predict the possibility of falls occurrence. This paper presents an extensive review of the state-of-the-art ‎trends and technologies of fall detection and prevention systems assisting elderly people and their ‎caregivers. Furthermore, this paper discusses the main challenges facing elderly fall prevention, along with ‎a comparison of various machine learning algorithms on the cStick dataset.
Keywords: Fall Detections; SVM; Fall Predictions; Elderly People, Etc